The study of the Consonant Phonemes and Vowel Phonemes Tai Dam Ethnic group in Xieng Kiaw Village, Kham District, Xieng Khouang Province - pheuaphom, singthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The study of the consonant phonemes and vowel phonemes Tai Dam ethnic group in Xieng Kiaw Village, Kham District, Xieng Khouang Province. The purpose of research is to study the consonant phonemes and vowel phonemes. The sample group used in this research is the people of Xieng Kiaw Village, Kham District, Xieng Khouang Province, who are qualified and have good knowledge of the Tai Dam language. The method of conducting the research is to collect data with a sample group using the actual interview method and then use the data to analyze it with the descriptive method according to the set objectives. The research results found that 1) The consonant phonemes has a total of 19 phonemes, the initial consonant has a total of 19 sound units and there are 7 sound units at the end of the syllable. 2) The vowel phonemes has a total of 24 sound units; Among them, there are 18 single sounds and 6 mixed sounds. There are also 4 special free sounds.